Poly lactic acid-quercetin nanoformulation synthesised using Syzygium cumini leaf extract improves the shelf life of tomato at room temperature. (16th March 2020) - Kumari, Avnesh; Yadav, Sudesh Kumar
Recently a novel approach has been developed for the synthesis of biodegradable nanoparticles (NPs) using plant leaf extracts. Following this approach, quercetin loaded poly lactic acid (PLA) NPs have been synthesised using Syzygium cumini leaf extract as surfactant/stabiliser. In the current study, developed biocompatible nanoformulation of PLA-quercetin was used for the first time to see its effect on shelf life of perishable fruits/vegetables like tomato. Nanoformulation treated tomatoes were evaluated for their total weight loss, total phenolic content, lycopene content, total sugar content, and quercetin content in comparison to untreated tomatoes. Developed nanoformulation was found to be effective in extending the shelf life of tomatoes by at least 10 d at room temperature relative to untreated and pure quercetin treated controls. Importantly, nutritional quality parameters were also maintained along with shelf life of tomatoes upon treatment with nanoformulation. Hence, the PLA-quercetin nanoformulation would be very useful to improve the shelf life of various perishable fruits and vegetables.